Effect of Addition of Vegetable Oils on Rumen Fermentation and Methanogenesis under In Vitro Conditions - Mahajan, Chetna; Mangal, Kajal; Wadhwa, M. (Indian Journal of Animal Nutrition, 2018)
This study was conducted to assess the effect of vegetable oils (VOs) viz., cotton seed, sunflower seed and castor seed oil on rumen fermentation and methanogenesis by using in vitro gas production technique. The oils were supplemented to the complete feed (oats fodder and concentrate mixture in 60: 40 ratio) @ 1, 2 and 3% (DM basis). The supplementation of VOs did not affect net gas production (NGP), however, the digestibility of NDF and true OM as well as ME availability decreased (P